Implementation of Epigenetic Variation in Sorghum Selection and Implications for Crop Resilience Breeding - Ketumile, Dikungwa; Yang, Xiaodong; Sanchez, Robersy; Kundariya, Hardik; Rajewski, John; Dweikat, Ismail M.; Mackenzie, Sally A. (Frontiers in Plant Science, 2022)
Crop resilience and yield stability are complex traits essential for food security. Sorghum bicolor is an important grain crop that shows promise for its natural resilience to drought and potential for marginal land production. We have developed sorghum lines in the Tx430 genetic background suppressed for MSH1 expression as a means of inducing de novo epigenetic variation and have used these materials to evaluate changes in plant growth vigor. Plant crossing and selection in two distinct environments revealed features of phenotypic plasticity derived from MSH1 manipulation. Introduction of epigenetic variation to an isogenic sorghum population, in the absence of selection, resulted in 10% yield increase under ideal field conditions and 20% increase under extreme low nitrogen conditions. However, incorporation of early-stage selection amplified these outcomes to 36% yield increase under ideal conditions and 64% increase under marginal field conditions. Interestingly, the best outcomes were derived by selecting mid-range performance early-generation lines rather than highest performing. Data also suggested that phenotypic plasticity derived from epigenetic variation was non-uniform in its response to environmental variability but served to reduce genotype x environment interaction. The MSH1-derived growth vigor appeared to be associated with enhanced seedling root growth and altered expression of auxin response pathways, and plants showed evidence of cold tolerance, features consistent with observations made previously in Arabidopsis. These data imply that the MSH1 system is conserved across plant species, pointing to the value of parallel model plant studies to help devise effective plant selection strategies for epigenetic breeding in multiple crops.